STRATEGI POLITIK PEMILIHAN KEPALA DAERAH : STUDI TERHADAP PEMILIHAN WALI KOTA PADANGSIDIMPUAN TAHUN 2018 - Puji Kurniawan (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2020)
This paper presents the results of elder research that the winning strategy is carried out using a kinship approach. This pair of candidates also conducted a survey or mapping of the indicators or criteria of a candidate for Mayor who was wanted by the people of Padangsidimpuan City, established a winning post in every sub-district in Padangsidimpuan City, formed a campaign team and winning team, and carried out an open campaign strategy which was held on June 23. 2018 at HM Nurdin Stadium. Supporting factors are the capacity, capability, quality and competence of the candidates for Mayor and Deputy Mayor, the vision and mission of the candidate pairs for Mayor and Deputy Mayor, expectations from the community for change and there are several excellent programs targeted by this pair of candidates Meanwhile, the inhibiting factor is competition to win the hearts of people and people who still think apathetic and lack insight.